2014
DOI: 10.1111/acem.12417
|View full text |Cite
|
Sign up to set email alerts
|

Troponin Elevations Only Detected With a High‐sensitivity Assay: Clinical Correlations and Prognostic Significance

Abstract: Objectives With clinical use of high‐sensitivity troponin I (hsTnI), more frequent troponin elevations will occur. However, the burden and implications of these elevations are not well understood. The authors quantified the prevalence of elevated hsTnI in patients presenting with possible acute coronary syndrome (ACS) who do not have elevated troponin with a current generation assay (cardiac troponin I [cTnI]) and determined the association of these newly detected elevations with a composite of all‐cause morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
1
39
0
1
Order By: Relevance
“…It is important to note that troponin levels may also be elevated in the blood of patients with a wide variety of other medical disorders. 84 Although these elevations reflect myocardial damage that is associated with poorer prognosis, the underlying mechanism for myonecrosis is not believed to be ischemic and varies by illness. It has also been recognized that even when MI has been excluded among patients who present to the emergency room with chest pain, low levels of troponin in blood, as detected by high-sensitivity assays, predict higher all-cause mortality and cardiac hospitalization in the months ahead.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that troponin levels may also be elevated in the blood of patients with a wide variety of other medical disorders. 84 Although these elevations reflect myocardial damage that is associated with poorer prognosis, the underlying mechanism for myonecrosis is not believed to be ischemic and varies by illness. It has also been recognized that even when MI has been excluded among patients who present to the emergency room with chest pain, low levels of troponin in blood, as detected by high-sensitivity assays, predict higher all-cause mortality and cardiac hospitalization in the months ahead.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…It has also been recognized that even when MI has been excluded among patients who present to the emergency room with chest pain, low levels of troponin in blood, as detected by high-sensitivity assays, predict higher all-cause mortality and cardiac hospitalization in the months ahead. 84 Although immunoassays are the method used in current troponin assays, extension to even more sensitive MS technologies may emerge in clinical practice. This could provide the opportunity to measure not only troponin levels but also protein modifications of sarcomere proteins that may correlate with disease.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…Both cardiac troponin I (cTnI) and cTnT assays are widely used and are considered diagnostically equivalent (1 ). In addition to diagnostic utility, cardiac troponin has prognostic value in both cardiac and noncardiac settings, including individuals with exacerbation of chronic obstructive pulmonary disease, sepsis, pulmonary embolism, and major noncardiac surgery (3)(4)(5)(6).…”
Section: © 2015 American Association For Clinical Chemistrymentioning
confidence: 99%
“…It was indicated that with high-sensitivity cardiac troponin assays, a rising cardiac troponin pattern would likely be seen in about 20% of ED patients (7 ). Thus, the number of patients needed to give a study the appropriate statistical power might be reduced.…”
mentioning
confidence: 99%
“…The FDA pointed out that they do not dictate the number of study participants, but rather that manufacturers need to substantiate their enrollment protocols with appropriately powered statistics to demonstrate equivalence to previously cleared assays. The FDA acknowledged that with high-sensitivity cardiac troponin assays, a larger number of patients with non-acute coronary syndrome myocardial injury will be detected, thereby decreasing the clinical specificity of these assays for AMI (7,10 ). We were of the impression that often the FDA expects all patients to be categorized as either having AMI or not having AMI despite the ambiguities described above.…”
mentioning
confidence: 99%